Rural Roads And Poor Area Development In Vietnam - Mu, Ren (The World Bank, 2007)
We assess impacts of rural road rehabilitation on market and institutional development at the commune level in rural Vietnam. Double difference and matching methods are used to address sources of selection bias in identifying impacts. We focus on impact heterogeneities and the geographic, community, and household factors that explain them. A key question from a policy standpoint is whether the impact-contingent factors are consistent and universal across project areas and outcome indicators. We find evidence of considerable impact heterogeneity, with a tendency for poorer areas to have conditions favoring higher impacts, although impacts are highly context specific